Analisis Terhadap Fatwa Mui No. 15 Tahun 2011 Tentang Penarikan, Pemeliharaan Dan Penyaluran Harta Zakat di Badan Amil Zakat Nasional - Ningsih, Sulistiya; Aprizal, Zulham (Blantika: Multidisciplinary Journal, 2025)
This study examines the concept of zakat muqayyad in the context of zakat management by the National Zakat Management Agency (BAZNAS) of Indragiri Hilir District, referencing the Fatwa of the Indonesian Ulema Council (MUI) No. 15 of 2011 on the Collection, Maintenance, and Distribution of Zakat Assets. The primary focus of the study is to analyze how the fatwa is implemented in practice and to assess the alignment of the collection and distribution of zakat muqayyad with sharia principles. A qualitative-descriptive method with a normative and empirical approach was employed. Data were collected through literature review, documentation, and interviews with BAZNAS managers and relevant stakeholders. The research findings indicate that zakat muqayyad at BAZNAS Indragiri Hilir is generally distributed in accordance with the provisions set by the zakat payers, while still adhering to the principles of fair distribution and public interest. Fatwa MUI No. 15 of 2011 serves as an important guideline in balancing the intentions of zakat payers and the needs of zakat recipients, as well as ensuring the accountability of zakat management by official institutions. This study recommends enhancing the dissemination of fatwas and strengthening internal regulations to ensure more effective and sharia-compliant zakat management.